Contamination of a high-cell-density continuous bioreactor - Domingues, Lucília (2000)
Continuous fermentations were carried out with a recombinant flocculent Saccharomyces cerevisiae strain in an airlift bioreactor. Once operating under steady state at a dilution rate of 0.45 h−1, the bioreactor was contaminated with Escherichia coli cells. The faster growing E. coli strain was washed out of the bioreactor and the recombinant, slower growing flocculating S. cerevisiae strain remained as the only species detected in the bioreactor. Flocculation, besides allowing for the realization of high-cell-density systems with corresponding unusual high productivity, may be used as a selective property for controlling some contamination problems associated with prolonged continuous operation.